Biological Role and Clinical Implications of microRNAs in BRCA Mutation Carriers - Tommasi, Chiara; Pellegrino, Benedetta; Boggiani, Daniela; Sikokis, Angelica; Michiara, Maria; Uliana, Vera; Bortesi, Beatrice; Bonatti, Francesco; Mozzoni, Paola; Pinelli, Silvana; Squadrilli, Anna; Viani, Maria Vittoria; et al. (Frontiers in Oncology, 2021)
Women with pathogenic germline mutations in BRCA1 and BRCA2 genes have an increased risk to develop breast and ovarian cancer. There is, however, a high interpersonal variability in the modality and timing of tumor onset in those subjects, thus suggesting a potential role of other individual’s genetic, epigenetic, and environmental risk factors in modulating the penetrance of BRCA mutations. MicroRNAs (miRNAs) are small noncoding RNAs that can modulate the expression of several genes involved in cancer initiation and progression. MiRNAs are dysregulated at all stages of breast cancer and although they are accessible and evaluable, a standardized method for miRNA assessment is needed to ensure comparative analysis of data and reproducibility of results. The aim of this review was to highlight the role of miRNAs as potential biomarkers for BRCA mutation carriers. In particular, biological and clinical implications of a link between lifestyle and nutritional modifiable factors, miRNA expression and germline BRCA1 and BRCA2 mutations are discussed with the knowledge of scientific evidence to date available.